Student Resource on Newton’s Law Concepts Reviewing from Gender: Identification Using Open-Ended Questions - Meiliani, Meiliani; Tanti, Tanti; Sulman, Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2021)
This article aims to find out the resources activated by students in solving Newton’s laws in terms of gender. This research is a quantitative descriptive study with two open test instruments. This research was conducted on 10th-grade students at SMK N 1 Muaro Jambi with 11 female students and 11 male students. The facts obtained in this study indicate that students’ thinking about Newton’s law is still lacking during the learning process. Based on the analysis results of the level of understanding of student concepts, female students understand better than male students. Overall, students fail to summon relevant knowledge when facing problems in the form of phenomena. In addition, they failed to use the knowledge they gained to answer questions. Students’ abilities are activated when they understand a phenomenon influenced by students’ original ideas from their personal experiences.